2006
DOI: 10.1186/1471-2407-6-22
|View full text |Cite
|
Sign up to set email alerts
|

Increased therapeutic potential of an experimental anti-mitotic inhibitor SB715992 by genistein in PC-3 human prostate cancer cell line

Abstract: Background: Kinesin spindle proteins (KSP) are motor proteins that play an essential role in mitotic spindle formation. HsEg5, a KSP, is responsible for the formation of the bipolar spindle, which is critical for proper cell division during mitosis. The function of HsEg5 provides a novel target for the manipulation of the cell cycle and the induction of apoptosis. SB715992, an experimental KSP inhibitor, has been shown to perturb bipolar spindle formation, thus making it an excellent candidate for anti-cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 28 publications
0
20
1
Order By: Relevance
“…15). In addition, enhanced apoptosis was shown for the KSP inhibitor SB-715992 and genistein (16). Contrary to our findings with SCH 2047069 and paclitaxel, combination studies reported previously with KSP inhibition and paclitaxel are reported to be antagonistic.…”
Section: Discussioncontrasting
confidence: 99%
“…15). In addition, enhanced apoptosis was shown for the KSP inhibitor SB-715992 and genistein (16). Contrary to our findings with SCH 2047069 and paclitaxel, combination studies reported previously with KSP inhibition and paclitaxel are reported to be antagonistic.…”
Section: Discussioncontrasting
confidence: 99%
“…Tumor cells that are arrested at a particular cell phase can be eliminated by more effective and less toxic strategies than when growth is completely out of control. Associated toxicities accompanying radiation and chemotherapy modalities have been reduced because of the genistein-induced arrest at the G2/M phase [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent inhibitors of the ATPase activity of KSP that have been reported include the dihydropyrimidine-2-thione derivative dimethylenastron [7,8], the quinazolinone derivatives ispinesib [9] and SB-743921 [10], the dihydropyrrole derivative MK-0731 [11], the tetrahydroquinoline derivative EMD-534085 [12], the cysteine derivative S-trityl-L-cysteine [13], and a biphenyl derivative [14]. Some of these KSP inhibitors have undergone clinical trials [10,15e21].…”
Section: Introductionmentioning
confidence: 99%